Determinants of plasma methylmalonic acid in a large population: implications for assessment of vitamin B12 status - Vogiatzoglou, A; Oulhaj, A; Smith, A; al., E (American Association for Clinical Chemistry, 2009)
BACKGROUND: Methylmalonic acid (MMA) in plasma or serum is widely used for assessment of vitamin B(12) status. However, data are sparse regarding factors, besides renal function, that may influence MMA concentrations. We searched for important determinants of plasma MMA in the general population. METHODS: In 6946 middle-aged (47-49 years) and elderly (71-74 years) individuals from the Hordaland Homocysteine Study in Norway, we collected anthropometric measurements, lifestyle data, and plasma MMA, vitamin B(12), and creatinine measurements. For 5820 individuals, we also collected dietary data. RESULTS: Age and plasma creatinine were positively associated with plasma MMA, whereas plasma vitamin B(12) was negatively associated. These variables together with sex were the strongest determinants of plasma MMA, accounting for 16% of the variation (R(2) = 0.16). Addition of anthropometric measures and lifestyle and dietary factors only gave slight improvement (total R(2) = 0.167). Increased plasma MMA was seen when plasma vitamin B(12) was <400 pmol/L. In individuals with vitamin B(12) >or =400 micromol/L (vitamin B(12)-replete), the 2.5th-97.5th percentile reference limits for MMA were 0.10-0.28 micromol/L (middle-aged) and 0.10-0.36 micromol/L (elderly). When plotted against creatinine (nomograms), the 97.5th percentile of MMA was similar in men and women but approximately 0.15 micromol/L higher in elderly than middle-aged individuals. Vitamin B(12)-replete participants had MMA upper limits approximately 0.1 micromol/L (elderly) and 0.04 micromol/L (middle-aged) below those of the unselected population at all creatinine concentrations. CONCLUSIONS: Identified determinants accounted for <17% of the overall variation in plasma MMA. The difference in MMA between middle-aged and elderly individuals is only partly explained by creatinine and vitamin B(12) concentrations.